Mandatory corporate law as an obstacle to venture capital contracting in Europe: Implications for markets and policymaking - Luca Enriques; Casimiro A. Nigro; Tobias Tröger (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2025)
Policymakers around the globe have sought to stimulate Venture Capital (VC) investments, and an extensive literature has inquired into the institutional determinants of a vibrant VC market, including corporate law. We contribute to that literature by exploring the significance of corporate law for VC contracting and hence VC investments. Corporate law's relative rigidity or flexibility is key to the efficiency of the contractual technology governing VC deals. Importantly, it can hamper such transactions through a number of "constraints," which we have identified in a companion paper. To illustrate our point, in another companion paper, we take German and Italian corporate laws as two case studies and show how they are largely averse to VC contracting. In addition, we show that the regulatory constraints they impose stem from blackletter corporate law much less often than from scholarly constructs and courts' interpretations. This chapter anticipates two objections that cast doubt over the importance of our findings as to the construction of vibrant VC markets in Germany and Italy. Specifically, the first of these objections is that VC funds and entrepreneurs planning to run their startups in Germany and Italy can circumvent the strictures of local corporate laws by incorporating abroad, and the other is that formal contracts are inconsequential in VC deals, meaning that the regulatory constraints we document are irrelevant. Meanwhile, the chapter also shows that the detailed understanding of regulatory constraints unveiled by our research can inform more effective policymaking. Ultimately, we make two policy recommendations: first, we propose the adoption of a statutory provision that would explicitly insulate the arrangements that typically shape U.S. VC deals from undue interventions; and, second, we argue in favor of a standard charter aligned with U.S. VC transactional practice that the law itself should declare entirely enforceable.
Keywords: G38; K22; L26; 330; Comparative Corporate Law; Comparative Corporate Governance; Entrepreneurship; Financial Contracting; Private Ordering; Startups; Venture Capital; Entrepreneurial Finance